hawaiispiders: Analyse Spider Evolution on Hawaii Island - Neves, Pedro (Zenodo, 2020)
Using the DAISIE framework, runs macroevolutionary analyses on the macroevolution of spider lineages on the Hawaii island, also known as Big Island. Explicitly accounts for the geodynamics of Hawaii.
See v0.0.0.9001 patch notes at: https://github.com/Neves-P/hawaiispiders/releases/tag/v0.0.0.9001
Keywords: island biogeography; macroevolution; evolutionary biology; spiders